2016
DOI: 10.1089/jamp.2014.1205
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Nasal Spray Deposition Pattern in Four Ethnic Groups

Abstract: Background: Very little is known about the role of nasal morphology due to ethnic variation on particle deposition pattern in the sinonasal cavity. This preliminary study utilizes computational fluid dynamics (CFD) modeling to investigate sinonasal airway morphology and deposition patterns of intranasal sprayed particles in the nose and sinuses of individuals from four different ethnic groups: African American (Black); Asian; Caucasian; and Latin American. Methods: Sixteen subjects (four from each ethnic group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 60 publications
3
40
0
Order By: Relevance
“…S. Cheng et al, 1996;Cheng, 2003;Garcia, Tewksbury, et al, 2009;Kesavan et al, 2000;Kesavanathan & Swift, 1998;Kesavanathan, Bascom et al, 1998;Rasmussen et al, 2000;Wiesmiller et al, 2003). Recently, investigations using CF-PD modeling methodology also predicted subject variability in nasal deposition (Dastan et al, 2014;Garcia, Schroeter, et al, 2009;Keeler et al, 2016;Wang et al, 2008). A number of attempts have been made to define functional correlations for nasal deposition with geometrical parameters like nostril shape and dimension, minimum cross-sectional area, and ⧹ or transnasal pressure drop (Cheng et al, 1991;Y.…”
Section: Introductionmentioning
confidence: 99%
“…S. Cheng et al, 1996;Cheng, 2003;Garcia, Tewksbury, et al, 2009;Kesavan et al, 2000;Kesavanathan & Swift, 1998;Kesavanathan, Bascom et al, 1998;Rasmussen et al, 2000;Wiesmiller et al, 2003). Recently, investigations using CF-PD modeling methodology also predicted subject variability in nasal deposition (Dastan et al, 2014;Garcia, Schroeter, et al, 2009;Keeler et al, 2016;Wang et al, 2008). A number of attempts have been made to define functional correlations for nasal deposition with geometrical parameters like nostril shape and dimension, minimum cross-sectional area, and ⧹ or transnasal pressure drop (Cheng et al, 1991;Y.…”
Section: Introductionmentioning
confidence: 99%
“…Further, while studies investigating nasal airflow dynamics have demonstrated that the morphology of the external nasal apparatus affects the direction and magnitude of the inspiratory airstream (Churchill, Shackelford, Georgi, & Black, 2004;Keeler, Patki, Woodard, & Frank-Ito, 2016;Mlynski, Gr€ utzenmacher, Plontke, Mlynski, & Lang, 2001;Segal, Kepler, & Kimbell, 2008), all research points to the internal nasal fossa (Figure 1) as the primary site of heat and moisture exchange within the nasal complex (Cole, 1982;Elad, Wolf, & Keck, 2008;Ingelstedt, 1956;Keck et al, 2000;Naftali et al, 2005).…”
mentioning
confidence: 99%
“…To a large degree, this can be attributed to the fact that the majority of studies related to climatic adaption in human nasal morphology have focused on a single morphofunctional unit (Carey & Steegmann, 1981;Cottle, 1955;Crognier, 1981aCrognier, , 1981bDavies, 1932;Franciscus & Long, 1991;Hiernaux & Froment, 1976;Schlager & R€ udell, 2015;Thomson, 1913;Thomson & Buxton, 1923;Weiner, 1954;Woo & Morant, 1934;Yokley, 2009), preventing direct comparisons across different components of the nasorespiratory tract. Moreover, while clinical studies of nasal physiology have routinely investigated the differential contributions of morphofunctional units to overall nasal function (e.g., Cole, 1982;Elad, Liebenthal, Wenig, & Einav, 1993;Naftali et al, 2005;Segal et al, 2008;Zhao & Jiang, 2014), few have incorporated information regarding ecogeographic variation in morphology (but see Keeler et al, 2016;Zhu, Lee, Lim, Lee, & Wang, 2011). Moreover, while clinical studies of nasal physiology have routinely investigated the differential contributions of morphofunctional units to overall nasal function (e.g., Cole, 1982;Elad, Liebenthal, Wenig, & Einav, 1993;Naftali et al, 2005;Segal et al, 2008;Zhao & Jiang, 2014), few have incorporated information regarding ecogeographic variation in morphology (but see Keeler et al, 2016;Zhu, Lee, Lim, Lee, & Wang, 2011).…”
mentioning
confidence: 99%
“…Ethnic differences in nasal physiology have been suggested to impact nasal spray deposition. 26 However, we did not stratify patients for this potential difference in this study. A potential study limitation was that this was a 1-day study, so it is possible that preferences may change over time.…”
Section: Discussionmentioning
confidence: 96%